Evaluation of Body Mass Index as a Factor of Outcome in Coronary Artery Bypass Surgery (Cardiovascular Journal, 2018)
Background: Obesity is supposed to be a risk factor for patients undergoing coronary artery bypass surgery (CABG) increasing risk of in-hospital mortality and postoperative morbidity. So, this study was conducted to evaluate the outcome of CABG in obese patients in Bangladesh.Methods: This prospective clinical trial was undertaken in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from January 2015 to December 2016. A total of 60 consecutive patients were selected for CABG operation and their outcome measured against pre-set variables. Body mass index (BMI) 25kg/m2was considered as cut off value between obese and non-obese patients.Results: Mortality after CABG surgery was 9.5% in obese group and 10.3% in non-obese group (p= 0.976) showing no significant difference but average hospital stay was more in obese group (10.2 + 25 days) than non-obese group (8.3 +3.7 days), p=0.489. Sternal would infection (50.0% &8.69%) and conduit harvest site infection (35.7% &4.34%) is also more in obese group but not significant statistically (p= 0.064 & 0.084 respectively).Conclusion: Patients with a BMI higher than normal are not at greater risk of in-hospital mortality after CABG. But obese patients should be more cared in post operative period for sternal and conduit harvest site infection as infection is more in obese patients.Cardiovasc. j. 2018; 10(2): 150-157